Media Sosial Menjadi Strategi Politik Masa Kini - Julius Manahara Hutabarat (Jurnal Pendidikan Agama dan Teologi, 2024)
Social media has become an effective tool in political campaigns. Politicians can use social media to promote themselves, disseminate information, and interact directly with voters. Social media also allows political parties to gauge public sentiment, understand voter needs, and respond with relevant policies. However, there are several challenges in using social media as a campaign tool, such as the spread of invalid information, the use of bot accounts, and the manipulation of opinions. Therefore, it is important for politicians and political parties to manage social media well and ensure that the information disseminated is correct and accountable. In addition, social media can also strengthen political polarization and reduce the ability to reach political agreements. Despite this, social media remains an effective tool in political campaigns, and its use continues to grow in Indonesia.